Piano Sonata no. 16 in G major, op. 31, no. 1, edited by Bartók - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Bartók, Béla, 1881-1945 (editor):::Contributor:::::::::::: (Budapest; Rózsavölgyi és Társa; Hungary, 2023)
Separate issue of the Piano Sonata no. 23 in F minor, op. 57, edited by Béla Bartók and published in Budapest by Rózsavölgyi és Társa between 1909-1912.